https://doi.org/10.36873/agp.v20: PERSEPSI PETANI SAYURAN LAHAN GAMBUT TERHADAP PENGEMBANGAN SISTEM PERTANIAN BERKELANJUTAN DI KELURAHAN KALAMPANGAN KECAMATAN SABANGAU KOTA PALANGKA RAYA (Perception Of Peatland Vegetables Farmers On The Development Of Sustainable Agricultural Systems In K, Sunaryati, R.,1) - Admin journal (Fakultas Pertanian Universitas Palangka Raya, 2019)
ABSTRACTThe land in the Kalampangan sub-district of Sabangau District is land that is dominated by peat soils.Peat binds to a relatively large amount of carbon that is formed in a long process and under watersaturated conditions. Water-saturated conditions cause the weathering process of organic matter to beimperfect, so that the remains of organic matter such as litter, roots. The land in the KalampanganVillage is a wetland with a layer of peat composed of organic material with a high C content thatexceeds carbon content in the terrestrial ecosystem. The aim of the study is to analyze the perceptionsof vegetable farmers towards the development of sustainable peatland agriculture. The studypopulation was all 164 vegetable farmers, the sample size was carried out by the Slovin techniqueaccording to Sugiyono (2011) with a total sample of 35 people. Analysis of the data used in the formof qualitative data and quantitative data. Sourced from primary data and secondary data. Using aLikert scale which is translated into sub-variables then sub-variables are translated again intomeasured indicators. The results of the research and analysis conducted on peatland vegetable farmers'perceptions of the development of sustainable agriculture in the Village of Kalampangan are